AB0488 Nailfold videocapillaroscopy and laser speckle contrast analysis: in search of a correlation between microvascular damage and blood perfusion. (23rd January 2014) - Ruaro, B.; Sulli, A.; Bernero, E.; Ravera, F.; Pizzorni, C.; Seriolo, B.; Cutolo, M.
Abstract : Background: Microvascular impairment and decreased peripheral blood perfusion are typical aspects of systemic sclerosis (SSc) (1, 2 ). It is not clear if there is a correlation between nailfold microangiopathy and blood perfusion (BP) in different skin areas of the body in SSc patients. Objectives: The aim of this study was to identify, in SSc patients, possible correlations between nailfold microangiopathy extent and BP degree in three different body areas (periungual, dorsum of hand and zygoma). Methods: Fifty SSc patients (mean age 57±10SD years) were enrolled after written informed consent. All patients were assessed by nailfold videocapillaroscopy (NVC) to assess the proper pattern of microvascular damage ("early", "active", or "late"), and calculate the microangiopathy evolution score (MES) (3 -5 ). BP was analysed by the new technique laser speckle contrast analysis (LASCA) by creating regions of interest (ROIs) at the periungual areas of the fingers, dorsum of hands and zygomas bilaterally: the average perfusion was scored as perfusion units (PU) (6 ). Patients enrolled into the study were not taking vasoactive drugs since at least one month before LASCA assessment. Non-parametric tests were used for the statistical analysis. Results: A statistically significant progressive decrease of BP was observed by LASCA in SSc patients with different "early", "active", or "late" NVC pattern of microangiopathy at the level of periungual areas (p<0.001). No statistically significant difference was observed between the three NVC patterns and BP at the level of both dorsum of hands and zygomas. A significant negative correlation was confirmed between MES and BP at periungual area (r=-0.48, p<0.0001). On the contrary, no statistically significant correlation was found between MES and BP at the level of both dorsum of hands and zygomas. Conclusions: A significant correlation between nailfold microangiopathy extent (evaluated by NVC) and BP degree (evaluated by LASCA) seems to exist in SSc patients at the periungual level, but not at dorsum of hands and zygomas. References: Cutolo M, et al. Nat Rev Rheumatol 2010; 6, 578-87. Murray AK, et al. Arthritis Rheum 2006; 54: 1952-60. Sulli A, et al Arthritis Rheum. 2012; 64: 821-5. Sulli A, et al. Ann Rheum Dis 2008; 67:885-7. Smith V, et al. Ann Rheum Dis 2010; 69:1092-6. Draijer M et al. Laser Med Sci 2009; 24: 639-51. Disclosure of Interest: None Declared